2010
DOI: 10.1038/ajh.2009.263
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue–Specific Regulation of Angiotensinogen in Obese Humans and Mice: Impact of Nutritional Status and Adipocyte Hypertrophy

Abstract: BACKGROUND The adipose tissue renin–angiotensin system (RAS) has been implicated in the pathophysiology of obesity and dysfunction of adipose tissue. However, neither regulation of angiotensinogen (AGT) expression in adipose tissue nor secretion of adipose tissue–derived AGT has been fully elucidated in humans. METHODS Human subcutaneous abdominal adipose tissue (SAT) biopsies were performed for 46 subjects with a wide range of body mass index (BMI). Considering the mRNA level of AGT and indices of body fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 18 publications
3
85
1
4
Order By: Relevance
“…In rodent models, angiotensin II contributes to adipose tissue proliferation by binding on both AT1 and AT2 receptors (Kouyama et al 2005;Yvan-Charvet et al 2009), which is opposed by angiotensin 1-7 acting on Mas receptors (Santos et al 2008). Although data about AGT expression in subcutaneous adipocytes of obese and non-obese human patients remain controversial (Dusserre et al 2000;Yasue et al 2010;Okada et al 2010;Oberbach et al 2014;Van Harmelen et al 2000a, b), the plasma levels of circulating angiotensinogen have been found increased in obese patients ) and they were shown to decrease with the weight loss (Engeli et al 2005;Oberbach et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In rodent models, angiotensin II contributes to adipose tissue proliferation by binding on both AT1 and AT2 receptors (Kouyama et al 2005;Yvan-Charvet et al 2009), which is opposed by angiotensin 1-7 acting on Mas receptors (Santos et al 2008). Although data about AGT expression in subcutaneous adipocytes of obese and non-obese human patients remain controversial (Dusserre et al 2000;Yasue et al 2010;Okada et al 2010;Oberbach et al 2014;Van Harmelen et al 2000a, b), the plasma levels of circulating angiotensinogen have been found increased in obese patients ) and they were shown to decrease with the weight loss (Engeli et al 2005;Oberbach et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Locally acting RAS contains all components of RAS, including angiotensinogen (Agt), renin, and angiotensin-converting enzyme (ACE) together with AT 1 and AT 2 receptors (Cassis et al 2008) to produce the main effector of the system, angiotensin II (Ang II). While Agt is produced mainly in the liver of lean individuals, adipose tissue is another important source of Agt in obese individuals (Yasue et al 2010). The specific feature of adipose tissue RAS is its ability to produce Ang II not only via the renin and ACE pathway but also through cathepsins and chymase (Karlsson et al 1998).…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…The over-production of ROS and upregulation of TNF-α are implicated in the impairment of glucose uptake (Shiuchi et al, 2004;Wei et al, 2008a). The RAS components, angiotensinogen (AGT), angiotensinogen converting enzyme (ACE) and angiotensin II type 1 receptor (AT1), are expressed in adipose tissue (Cassis et al, 2008;Engeli et al, 2000;Kalupahana and Moustaid-Moussa, 2012;Yasue et al, 2010) and skeletal muscle (Johnston et al, 2011;Jones and Woods, 2003;Kadowaki et al, 2006;Vermes et al, 2003) suggesting that an imbalance between systemic and local RAS has the potential to exacerbate metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%